2001
DOI: 10.4049/jimmunol.167.12.7038
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Release of IL-18 Binding Protein in Response to IFN-γ

Abstract: IL-18 and IL-18 binding protein (IL-18BP) are two newly described opponents in the cytokine network. Local concentrations of these two players may determine biological functions of IL-18 in the context of inflammation, infection, and cancer. As IL-18 appears to be involved in the pathogenesis of Crohn’s disease and may modulate tumor growth, we investigated the IL-18/IL-18BPa system in the human colon carcinoma/epithelial cell line DLD-1. In this study, we report that IFN-γ induces expression and release of IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 39 publications
6
94
1
1
Order By: Relevance
“…Healthy or RA PBMCs constitutively produced significant levels of IL-18BP. The increased expression and release of IL-18BP in response to IFN␥ has been reported (15). However, the addition of IL-12 decreased IL-18BP production from PBMCs in spite of increasing IFN␥ production in the same culture.…”
Section: Il-18bp Production In Ramentioning
confidence: 71%
“…Healthy or RA PBMCs constitutively produced significant levels of IL-18BP. The increased expression and release of IL-18BP in response to IFN␥ has been reported (15). However, the addition of IL-12 decreased IL-18BP production from PBMCs in spite of increasing IFN␥ production in the same culture.…”
Section: Il-18bp Production In Ramentioning
confidence: 71%
“…Elevated levels of IL-18BP are found in serum of patients suffering from septic shock and IL-18BP is expressed in response to IFNg. 13 Several isoforms have been discovered resulting from alternative mRNA splicing of which IL-18BPa and IL-18BPc exhibit the highest affinity towards IL-18. 14 These isoforms are able to neutralize 495% of the biological activity of IL-18 at a 1:1 molar ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Besides T cells and natural killer cells, human dendritic cells (DC) are also capable of potently releasing IFNg under the influence of IL-18 (3,10). IL-18 biological activity seems to be controlled by an IFNginduced negative feedback loop mediated by the IL-18 opponent IL-18 -binding protein (11). Interestingly, it has recently been shown that IL-18 was able to induce the maturation of human monocyte -derived dendritic cells with regard to biochemical as well as functional characteristics (12).…”
Section: Introductionmentioning
confidence: 99%